Cooling adhesive tape - ZHAO YANG (2017)
The invention discloses a cooling adhesive tape. A metal net covers a plastic film substrate and is bonded through an adhesive layer, wherein the metal net is preferably a copper net; an adhesive is preferably acrylic acid pressure sensitive adhesive; and the substrate is preferably a PET film. The cooling adhesive tape has three functions of bonding, heat conduction and electromagnetic shielding (antistatic), reduction of the thickness of an electronic product is facilitated, the manufacturing complexity of the electronic product can be reduced, and improvement of the production efficiency of an electronics manufacturer is facilitated. A metal wire has good electrical conductivity and thermal conductivity at the same time, and the requirements of two aspects are considered. 本发明公开了种散热胶带，其在塑料薄膜基材上覆盖有金属网，并通过粘结剂层相粘合。其中金属网优选铜网，粘结剂优选丙烯酸压敏粘结剂，基材优选PET薄膜。根据本发明实施的散热胶带兼具了粘合、热传导、电磁屏蔽(抗静电)这三项功能，既有利于减少电子产品的厚度，也可降低电子产品的制造复杂程度，有助于电子产品生产厂家提高生产效率。金属丝同时具有良好的导电性和导热性，兼顾了两方面的需求。